Teacher Feedback Technique in Students’ English Writing: A Study of Descriptive Texts Among X-Grade Students at SMA N 15 Semarang - Nugroho, Dwi Setyo Permadi; Sukmaningrum, Rahmawati; Setyorini, Ajeng (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2025)
Teacher feedback plays an important role in improving student’s writing skill. This study aimed to analysis the feedback technique given by the teacher and the reason for its application. This research was a descriptive study designed to provide a detailed explanation of the implementation of feedback technique given by the teacher at SMA N 15 Semarang. In addition, the data was collected using two instruments; document and interview. There were two finding of the research. Firstly, teacher used the minimal marking technique to provide feedback to students. The feedback provided was intended to help students work on their grammatical errors or writing form using symbol to shorten the correction, such as “P” for punctuation, “Cap” for capitalization, “Spell” for spelling, and etc. Secondly, the teacher employed this technique because it was effective and time-saving. Additionally, it also helps students to understand easily their mistakes. However, as the study used a small sample size, the results require further exploration. Therefore, the minimal marking technique could be applied more broadly in EFL classroom to assess its wider effectiveness.